Trafficking of Women for Sexual Exploitation in Europe: Prosecution, trials and their impact - Meshkovska, Biljana; Mickovski, Nikola; Bos, Arjan; Siegel, Melissa (Anti-Trafficking Review, 2016)
The importance of criminal proceedings against traffickers in the fight against human trafficking is clear. However, this paper illustrates that investigations, prosecutions and trials are often extremely long with mixed influences on the victims themselves. The study draws on fieldwork conducted in five European countries: Albania, Bosnia Herzegovina, Bulgaria, Serbia and the Netherlands. A total of 40 interviews were conducted—with 7 trafficked persons and 33 service providers who are in direct contact with victims. Based on these interviews, some general themes were identified for analysis: (1) length of the criminal justice process, (2) secondary victimisation, (3) need for specialist training and interviewing skills for all individuals in contact with trafficked persons, (4) information and trust, (5) protection from intimidation, (6) not just conviction but financial compensation, and finally, (7) the label ‘victim’ and the wish to testify. Each theme is discussed in detail.